2008
DOI: 10.1007/s11605-007-0457-8
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of Ostomy Takedown

Abstract: Takedown of a temporary ostomy has a low mortality but a nonnegligible morbidity. The stoma location (large vs. small bowel) has a higher impact than the type of stoma construction (end vs. loop) on the incidence and severity of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 21 publications
(19 reference statements)
1
73
1
7
Order By: Relevance
“…Morbidity related to stoma closure can vary from 0% to 38.5% (mean 17.3%) and mortality can vary from 0% to 8.9% (0.4%) in a recent review including 48 studies [40,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity related to stoma closure can vary from 0% to 38.5% (mean 17.3%) and mortality can vary from 0% to 8.9% (0.4%) in a recent review including 48 studies [40,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons use a protective stoma after LAR to prevent anastomotic leakage in the hope that by diverting the fecal stream and keeping the anastomosis free of material, leakage will be less likely. While other surgeons have reported that covering the protective stoma had no influence on anastomotic leakage and reoperation rates, the further complications that can be caused by the stoma itself should not be ignored, as they include discomfort and inconvenience, high output with consequent dehydration, and anastomotic complications at the stoma closure site [12][13][14][15][16][17][18] . Although protective stomas are widely used in LAR for rectal cancer, it remains unclear whether such protective stomas are useful for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the temporary protection of ileoanal and coloanal/ rectal anastomoses is often achieved by the creation of a loop ileostomy [1]. Although defunctioning of the colon does not provide true prophylaxis against anastomotic leakage, it is meant to mitigate potential complications after anastomosis formation.…”
Section: Introductionmentioning
confidence: 99%